Interconnecting language to culture: Building a local wisdom-based activity book for English teaching of primary schools in Indonesia - Santhy Hawanti; Lia Mareza; Lutfi Istikharoh; Dewi Santri; Novan Andrianto; Nur Aisyah (Universitas Muhammadiyah Purwokerto, 2026)
The aim of this project was to integrate the learning process in Banyumasan culture for designing and evaluating the local wisdom-based Students' Activity Book (SAB) for basic English instruction in Indonesia. This study has a number of steps, including need analysis, design, expert validation, and field testing, utilizing a Research and Development (R&D) approach based on Borg and Gall's model. Three main themes originate from the analysis of the results: pedagogical effectiveness, product feasibility, and needs analysis and cultural relevance. Teachers, according to starting polls, believe that local culture should be incorporated into English learning materials because textbooks that only emphasize Western culture often discourage students from learning the language. Expert validation showed an agreement rate of 88 percent, indicating that the Students’ Activity Book was appropriate to be used. The materials, including local stories such as The Legend of Baturraden and traditional foods like mendoan, were considered ideal supports for both language and cognitive development among young learners. The field trial also showed that students using the book achieved a higher N-Gain score (0.72) than those in the control group (0.45). These findings suggest that connecting English learning with students’ cultural background makes learning more meaningful and effective. This study offers a glocalized model that combines global English learning with local identity in line with the Kurikulum Merdeka, and highlights the importance of local wisdom in improving language skills while preserving cultural pride.